2016
DOI: 10.1177/002795011623600102
|View full text |Cite
|
Sign up to set email alerts
|

Britain's influence in the EU

Abstract: How much influence does the UK have in Europe? How has this changed? We argue that the UK has tended to view its relationship with the EU in transactional terms, and that this has led to a dominant understanding framed in terms of 'costs' and 'benefits.' However, thinking more broadly gives a more nuanced picture of British influence. Thus, we approach this question from two directions: examining the historical record of the UK's role in the development of the EU and the single market; and looking at the ways … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…In other words, based on rationalist assumptions, Italy constitutes a theoretical anomaly or a deviant case (Gerring and Seawright, 2008, p. 302). Additionally, the impact of domestic dynamics on Italy's effectiveness at the EU level remains under‐researched compared to other large member states, such as Germany (Bulmer, 2014) or the United Kingdom (Menon, 2004; Menon and Salter, 2016). Therefore, a theoretical framework that better accounts for the influence of domestic factors is needed to capture the puzzling variation in Italy's performance at the EU level.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In other words, based on rationalist assumptions, Italy constitutes a theoretical anomaly or a deviant case (Gerring and Seawright, 2008, p. 302). Additionally, the impact of domestic dynamics on Italy's effectiveness at the EU level remains under‐researched compared to other large member states, such as Germany (Bulmer, 2014) or the United Kingdom (Menon, 2004; Menon and Salter, 2016). Therefore, a theoretical framework that better accounts for the influence of domestic factors is needed to capture the puzzling variation in Italy's performance at the EU level.…”
Section: Methodsmentioning
confidence: 99%
“…If these contributions have the merit of emphasizing the importance of national administrative structures, the European integration literature focusing on member states' domestic politics has clearly shown that domestic political dynamics contribute to shaping the performance of member states in EU negotiations. From larger countries like Germany (Bulmer, 2014;Bulmer and Paterson, 2013), France (Dehousse and Menon, 2009;Dimitrakopoulos et al, 2009) and the UK (Menon and Salter, 2016) to smaller ones such as Belgium and Sweden (Beyers and Trondal, 2004), domestic politics matter for a member state's influence over EU negotiations. During the peak of the Eurozone crisis, the internal divisions within the German coalition government significantly constrained Merkel's ability to assume a leadership role at the EU level (Bulmer, 2014(Bulmer, , p. 1257.…”
Section: The Best Of All Worlds? a Unitary Framework To Account For M...mentioning
confidence: 99%
“…The UK's relationship with the EU has historically been determined by a complex interplay between political and economic interests framed in terms of costs and benefits of the EU membership (Jensen and Snaith, 2016; Menon and Salter, 2016). The bulk of the EU's spending in the UK is for agriculture -the European Agricultural Guarantee Fund is the largest fund (Keep, 2018).…”
Section: Theoretical Backgroundmentioning
confidence: 99%